2011
DOI: 10.1111/j.1467-9299.2011.02007.x
|View full text |Cite
|
Sign up to set email alerts
|

‘…i Take Political Responsibility!’: The Theoretical and Empirical Relation Between Ministerial Responsibility and Ministerial Resignations in Germany

Abstract: How is the doctrine of ministerial responsibility applied in the decisions of German ministers (not) to resign? This question arises from an empirical puzzle as well as from a theoretical contradiction. Despite the prominent principle of ministerial responsibility, empirically, the ‘personal consequences' of ministerial scandals in their area of responsibility, display a large variance. Some ministers resign because of rather trifling affairs, others stay in office in spite of serious scandals. Taking into con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…As expected at the outset of this study, the two theoretical perspectives applied complement each other in several ways and the implications of this study are straightforward. It is widely acknowledged that blame management studies need to better include contextual factors (e.g., individual, institutional, cultural and situational) in the analysis to help explain why blame processes develop as they do (Boin ; Fischer ; Hansen et al. ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As expected at the outset of this study, the two theoretical perspectives applied complement each other in several ways and the implications of this study are straightforward. It is widely acknowledged that blame management studies need to better include contextual factors (e.g., individual, institutional, cultural and situational) in the analysis to help explain why blame processes develop as they do (Boin ; Fischer ; Hansen et al. ).…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies of ministerial careers in European countries, including Sweden, indicate that ministers resign when they are forced to and not because of formal constitutional accountability mechanisms (Bäck et al. ; Fischer ; Svedin ). Factors both inside and outside the cabinet, such as accountability pressures from external arenas and understanding the context of specific resignations need to be examined (Fischer ; Hansen et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hinterleitner's (2020) comparative case-study across three political regimes with different institutional arrangements for ministerial responsibility confirms this effect. However, many studies have found that the link between formal accountability rules, such as ministerial responsibility, and forced resignations is imperfect at best (Berlinski et al, 2012;Fischer, 2012;Thompson & Tillotsen, 1999;Woodhouse, 1994). Fischer (2012, p. 616) goes even further in a later analysis of 133 German resignation issues, concluding that "the stronger the link between a resignation issue and ministerial responsibility, the less likely is a resignation" (original emphasis).…”
Section: Institutional Accountability: the "Corrective Effect" In Sin...mentioning
confidence: 99%
“…In the end, it also led to consequences in terms of the resignation of the 'deputy', but importantly not of the Minister of Foreign Affairs himself. There is no direct formal relationship between political accountability to parliament and the consequence in terms of the resignation of the 'deputy', and Germany does not have a formal rule of parliamentary no-confidence votes as they do in the Nordic countries (Fischer, 2012). However, if the opposition (political, external) and especially the media (social) had not been able to use this window of opportunity to demand information and debate, legal accountability would not have affected government's policy at all.…”
mentioning
confidence: 99%